Method for Suspicious Object Search in Video from an Aircraft Camera Based on Histogram Analysis - Чирков, А.В.; Приставка, П.О. (Science-based technologies, 2018)
A problem of particular object search on video which arises in some practical tasks can be solved by known methods if a sample image database is available. In case of its absence it is possible to find suspicious objects by heuristic approaches. But such approaches are not fast enough, thus they cannot be used in real-time systems. We propose a histogram-based method for target (suspicious) object search in video from an aircraft camera which is appropriate for usage in real-time systems.